A STUDY ON THE READING ABILITY OF THE THIRD YEAR STUDENTS OF SMPN 3 TAMBANG IN COMPREHENDING ENGLISH LEGENDS - Suri Nurmaini; Masyhur Masyhur; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was designed to describe the student’s reading ability in comprehending english legends and aimed to find out the students ability in comprehending English Legends for each component. This research was conducted in SMPN 3 Tambang that has been collected from September to Oktober 2017. The try out class was IX.6 (31 students) and the sample was IX.7 (32 students) chosen by cluster random sampling. The result showed that the ability of the third year students of SMPN 3 Tambang in comprehending English Legend for each component was in good level whose mean score was , however, the students have not passed the minimum score of the school which is 76. For the level of remembering; finding factual information the mean score was 84.38, finding references was 72.9, finding meaning of difficult words was 67.2. The level of understanding (finding restatement) the mean score was 67.19 and for the analyzing level (finding main idea) the mean score was 81.77. Therefore, this research suggests the English teachers to focus on the levels and components that students still find such difficulities that they are into poor level. Students should learn the components in English legend and other text types. Further researchers are expected to find the standard guidance of classification of Bloom’s Revised Taxonomy indicated the components of reading comprehension.Key Words: Student’s Ability, Comprehending, English Legends.